Marketing of Tourism Products in Karnataka: Policy Implications - Ramakrishna, H. (Indian Journal of Marketing, 2011)
The boom in travel and tourism is directly or indirectly helping the improvement of the socio and economic conditions of the stakeholders such as hoteliers, resort owners, tour and travel operators, guides and other dependents. The tourism sector is making a significant contribution to the state economy. Therefore, it needs to be well nurtured by making a proper policy on tourism sector by the central as well as the state governments. Though the tourism is not a State's related issue in India, however, the areas like application of luxury tax on the accommodates, issue of certificates and licenses related to establishment of tour and travel related activities etc, come under the purview of state government control. Therefore, in the development of the tourism sector, the role of States in the democratic set up of India needs to be recognized. Each state is responsible for making a proper policy on tourism on par with the National Tourism Policy to attract more number of tourists to their respective states. It is also the responsibility of the concerned State to exhibit the various tourism products available in the state. The policy of tourism should be in such a direction. The state government's initiations in marketing the tourism products are evaluated in this article.